Deradikalisasi Pemikiran Agama di lingkungan PTKIN Melalui Penguatan Mata Kuliah Perbandingan Madzhab: Studi pada Mahasiswa di UIN Prof. K.H. Saifuddin Zuhri Purwokerto dan UIN Sunan Kalijaga Yogyakarta - Basith, Abdul; Labib, Mughni (Jurnal Syariah dan Hukum Komparatif, 2022)
Radicalism is a religious ideology it’s characterized is intolerant to diversity and differences that occur in religious and life state, so that it threatens the integrity and upholding of the Unitary State of NKRI. One of the causes of radicalism that can be embedded in individuals in society is because of the wrong understanding of religious teachings received from sources that cannot be accounted for. One of the efforts that can be done in the framework of the deradicalization project, and counter radicalism (anticipation of radicalism) is to instill a religious ideology that is characterized by wasathiyyah, moderate, and tolerant to diversity and differences in teachings and cultures in society. It was through strengthening the comparative madhhab courses in the PTKIN environment, especially students of the comparative madhhab study program. Based on research conducted by researchers, it turns out that there is a strengthening of comparative madhhab courses, according to the students, it is able to influence them to have a moderate paradigm, although according to some lecturers they think it is still weak, and cannot be maximized, so it needs a lot of curriculum development, and also create a climate and culture of discussion about moderation among students on campuses